Pedampingan Potensi Ekonomi Usaha Mikro Syariah Serta Penerapan Produksi Berbudaya Lokal untuk Mengurangi Kemiskinan di Desa Galis Kecamatan Giligenting Kabupaten Sumenep - Atik Purmiyati; Lucy Dyah Hendrawati; Ely Rahmawati; Asan Ali Golam Hassan (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Galis Village is a village that has the potential for large marine catches and the potential for fishery resources in coastal areas is quite large. However, some people in the area are still below the poverty line. Galis Village has great potential in the fisheries sector. Therefore, there is a need for training or mentoring on the economic potential of sharia micro-enterprises (Baitul Maal Wat Tamwil and Sharia Cooperatives) in the community to increase economic potential and achieve the SDGs. This research uses data collection methods which include FGD (focus group discussion), SWOT analysis, and training. Based on the results of IFAS and EFAS calculations which show the position of Galis Village in quadrant 2, it shows that the weaknesses of Galis Village are greater than its strengths. Quadrant 4 also shows that the opportunities faced by Galis Village are greater than the threats they will receive. Therefore, action is needed to move the position of Galis Village to quadrant 1 by increasing its strengths and reducing its weaknesses. The strategy that Galis Village can carry out based on the SWOT Matrix is ​​to maximize the regional potential to produce unique goods.